Developing a Mobile Application-based System for Enhancing Medical Skill Training - TING-SHENG WENG; XUAN-REN CHEN (Journal of Advances in Medical Education and Professionalism)
Introduction: In a regional hospital in Southern Taiwan, an average of 25 heart surgeries are performed annually, with surgical education conducted one-on-one. This indicates thatopportunities for paramedics to participate in surgical procedures are quite limited. Although 80 paramedics in the hospital can perform surgical procedures, 69 have more than two years ofexperience, and only 19 are selected by surgeons to perform surgical procedures. Consequently, paramedics without hands-on experience are likely to feel panicked and helpless.Methods: The present study employed a systematic software development approach to create a mobile application-based medical skill training system. Initially, we conducted a comprehensiveneeds analysis through in-depth interviews with cardiac surgery nurses and administrators to accurately identify the key training requirements. In the system architecture design phase, we chose Windows Server as the operating system, combined PHP and Apache to handle web service requests, used MariaDB for data storage and management, and applied FastAPI to facilitate dataexchange with other services. Client-side development utilized the Flutter framework, ensuring a consistent user experience across iOS and Android platforms.Results: We also designed complex data structures to accommodate testing and recording needs, including exam data, question types, and option records. For user flow implementation, we developed a complete process including user registration, subject management, test preparation, and evaluation. Finally, we implemented core functionalities such as the login interface, question selection, and test interface to ensure the system’s comprehensiveness and practicality. This multi-stage development approach aimed to create an efficient, user-friendly, and adaptive training platform to meet the specific needs of cardiac surgery nursing staff.Conclusion: The development and implementation of the mobile application-based system for enhancing medical skill training has demonstrated significant potential in addressing the challenges of paramedics in cardiac surgery settings. While the initial results are promising, further long-term studies are needed to assess the impact on actual surgical outcomes and patient care quality.